Cisplatin induced acute mesenteric ischaemia: A case report and review of the literature. (2017) - Khosla, Shivun; Kennedy, Lauren; Abdulaal, Yasser
Highlights: Arterial thrombosis occurs in 2% of patients having Cisplatin-based chemotherapy. There is only one previous report detailing mesenteric ischaemia secondary to cisplatin. The mechanism relating to the development of arterial thrombosis is not understood. Benefit of prophylactic parenteral anticoagulation during cisplatin chemotherapy is unknown. Abstract: Introduction: Cisplatin is a platinum-based chemotherapeutic agent, widely used in cancer therapies for numerous solid tumours. It is becoming more recognised that a potentially life-threatening complication of cisplatin is accelerated arterial and venous thrombosis. Presentation of case: We describe a case of a 62 year-old with no risk factors for vascular disease who presented with thromboembolic acute mesenteric ischaemia of the small bowel during treatment with cisplatin for head and neck cancer. Discussion: We review the literature on the incidence and pathogenesis of cisplatin induced arterial thrombosis and discuss current treatment options of acute mesenteric ischaemia detailing our management of this case. Conclusion: Cisplatin increases the risk of arterial thrombosis and this case report details acute mesenteric ischaemia secondary to its use. We hope to raise clinician awareness of this sequelae which can occur even in patients in the absence of other identifiable risk factors.